2019
DOI: 10.1093/cid/ciz235
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Identifying Household Contacts of Rifampin-and Multidrug-resistant Tuberculosis Cases at High Risk of Progression to Tuberculosis Disease

Abstract: Background We assessed multidrug-resistant tuberculosis (MDR-TB) cases and their household contacts (HHCs) to inform the development of an interventional clinical trial. Methods We conducted a cross-sectional study of adult MDR-TB cases and their HHCs in 8 countries with high TB burdens. HHCs underwent symptom screenings, chest radiographies, sputum TB bacteriologies, TB infection (TBI) testing (tuberculin skin test [TST] and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Two are evaluating levofloxacin versus placebo: TB-CHAMP (ISRCTN92634082) and VQUIN MDR (ACTRN12616000215426), and the PHOENIx trial comparing the efficacy and safety of delamanid versus isoniazid (NCT03568383). We conducted a feasibility study in preparation for the PHOENIx trial The feasibility study evaluated index cases with reported MDR-TB and their HHCs at 16 sites, in eight high TB burden countries [ 3 ]. The objectives of the feasibility study were to (1) identify, recruit, and characterize adult MDR-TB index cases and their adult and child HHCs; (2) describe the prevalence of TB disease, TBI, and HIV among HHC; and (3) estimate the proportion of HHCs at high risk of TB and, therefore, potentially eligible for the interventional trial.…”
Section: Introductionmentioning
confidence: 99%
“…Two are evaluating levofloxacin versus placebo: TB-CHAMP (ISRCTN92634082) and VQUIN MDR (ACTRN12616000215426), and the PHOENIx trial comparing the efficacy and safety of delamanid versus isoniazid (NCT03568383). We conducted a feasibility study in preparation for the PHOENIx trial The feasibility study evaluated index cases with reported MDR-TB and their HHCs at 16 sites, in eight high TB burden countries [ 3 ]. The objectives of the feasibility study were to (1) identify, recruit, and characterize adult MDR-TB index cases and their adult and child HHCs; (2) describe the prevalence of TB disease, TBI, and HIV among HHC; and (3) estimate the proportion of HHCs at high risk of TB and, therefore, potentially eligible for the interventional trial.…”
Section: Introductionmentioning
confidence: 99%
“…A feasibility study was conducted to inform the design of the trial. 29 The results of the feasibility study suggest estimated parameters for the unstratified trial of 0 = 0.0645, m = 3.01, CV m = 0.75, and 0 = 0.0675. We use the conservative design effect F = F B = 1 + [ (CV 2 m + 1)m − 1 ] 0 and size the trial to have significance level = .05 and 90% power ( = 0.1) to detect a treatment effect of b = log(0.5) on the log-odds ratio scale.…”
Section: Example: Evaluating the Size Of A Tb Prevention Trialmentioning
confidence: 90%
“…Clusters are the contacts in the same household as the index patient who are considered at higher risk of themselves developing TB disease, potentially because of the exposure to the index patient. A feasibility study was conducted to inform the design of the trial …”
Section: Example: Evaluating the Size Of A Tb Prevention Trialmentioning
confidence: 99%
See 2 more Smart Citations